CALCULATION OF SEDIMENTARY DEPOSITS ELASTIC CONSTANTS IN TRICLINIC APPROXIMATION ACCORDING TO VSP DATA - Prodayvoda, G.; Vyzhva, S.; Kuzmenko, P.; Vyzhva, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This article attempts to define a complete component set of elastic constants tensor matrix in triclinic symmetry approximation and to evaluate the nature of seismic waves azimuthal anisotropy using field seismic surveys data. Elastic constants are determined by inverting the indicatrixes of radial and phase velocities with different polarization. Symmetry group of sedimentary strata is defined using acoustic tensor and elastic constants tensor. The basis of the standard acoustic coordinate system was the three right mutually orthogonal vectors of the acoustic tensor. Fedorov method is used for approximation of the elastic constants tensor to transversely isotropic medium, which provides not only a quantitative assessment of elastic constants matrix components but also allows us to estimate the deviation degree of real anisotropic medium elastic constants from those typical of transversely isotropic medium, the latter being the most similar to it.